Spinal Exostosis in a Boy with Multiple Hereditary Exostoses - Al Kaissi, Ali (Hindawi Publishing Corporation, 2013)
We report on a 13-year-old boy who presented with multiple hereditary exostosis and had development of back pain, associated with neurological deficits, and was found to have exostoses in the spinal canal. Spine radiograph showed a cauliflower-like abnormality of multiple exostoses of the posterior arch (pedicle) of the thoracic vertebrae (T3–5). Reformatted CT scanning revealed the simultaneous development of intra- and extraspinal osteochondromatosis of T3–5. The spinal cord was compressed by the intraspinal exostosis. Our patient was surgically treated for intraspinal exostoses and showed cessation of neurological deficits. We report what might be a rare association of spinal cord compression in a patient with multiple hereditary exostoses.